Remoteness and Real Exchange Rate Volatility. (IMF Working Papers; Working Paper ;, 2005)
This paper examines the impact of trade costs on real exchange rate volatility. The channel is examined by constructing a two-country Ricardian model of trade, based on the work of Dornbusch, Fischer, and Samuelson (1977), which shows that higher trade costs result in a larger nontradable sector. This, in turn, leads to higher real exchange rate volatility. We provide empirical evidence supporting the channel.